If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8h + -3 + -5h + -4 = 0 Reorder the terms: -3 + -4 + 8h + -5h = 0 Combine like terms: -3 + -4 = -7 -7 + 8h + -5h = 0 Combine like terms: 8h + -5h = 3h -7 + 3h = 0 Solving -7 + 3h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3h = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 3h = 0 + 7 3h = 0 + 7 Combine like terms: 0 + 7 = 7 3h = 7 Divide each side by '3'. h = 2.333333333 Simplifying h = 2.333333333
| 0.25(y+2)-0.15(y+3)=4 | | (-7)y+8+15y-14= | | 45x^3-5x+0=0 | | 10x^2-16+6=0 | | [4-(2-4(2-4)+6)]+3=-9 | | 0=-4+x^2 | | 0=4+x*x | | 0=4+x^2 | | x=4+x^2 | | 4m-12=m-6 | | P=11P | | 11-a=2a-6 | | Y-5=4(x-1) | | -1.8(1.03n+0.9)=2.2(2.58n+1.4)-1.4 | | 4.75=a+1.85 | | 1.30m=6.50 | | 6.50=m-1.30 | | 6.50=M+1.30 | | 2a+b=24 | | 2a+3b-a+4a= | | y=65x | | 3a+5a+a= | | (x^4+y^2)dx-(xy)dy=0 | | 14-(6-3r)=4r-r | | y=6y-8y | | 6x-3=x+7 | | 2m+15=8 | | W(a)=2afindw(3) | | H(a)=a^3findh(2) | | -3+2v-1+4=v-3 | | -4n+3n=-15+n+4+5 | | 4p+25=(6-3)-3(4-3p) |